Mercados e comercialização de produtos lácteos pela agricultura familiar nas feiras livres de Goiânia-GO - Segundo, Charla Basílio Schinaider (2023)
Products sold at free fairs historically originate from what is currently considered family farming, forming circuits of social interaction that enable the producer to establish relationships with consumers and between them and food. In this sense, the markets accessed by family farming can then be seen as strategic spaces in which new services and products can emerge, as well as practices – both productive and product commercialization – that are different from those found in the conventional system, having the potential to become consolidate, culminating in new processes of rural development. For this reason, this study was justified by the importance of analyzing the characteristics of the commercialization channels of dairy products accessed by family farming, especially free fairs, by the significant and traditional production of milk in the state of Goiás by family farming and in addition to this, the lack of data showing the role of family farming in relation to dairy products sold in these spaces, not only in Goiânia, but also in the state. From these perspectives, the present study aims to analyze strategies and dynamics of commercialization channels accessed by family farmers for the commercialization of dairy products at free fairs in Goiânia-GO. Specifically, the study intended to systematically review the literature on commercialization channels accessed by family agriculture and analyze how the commercialization of dairy products by family agriculture at free fairs in Goiânia is configured. After applying a questionnaire to all stallholders who sell dairy products at the 105 fairs in the capital of Goiás, it was found that the marketing of these products occurs, in large part, by middlemen, who purchase products both from other middlemen and directly from producers, which are manufactured within the state of Goiás or purchased in Minas Gerais. Of the 185 interviewees, 43 are producers of dairy products and of these, only 32 consider themselves family farmers, producing fresh milk, assorted cheeses, butter, and milk sweets, which are offered weekly at the free fairs in the capital. The results also reveal that, among producers, family farming has little autonomy to carry out direct sales, without the presence of middlemen. The products deserve attention and recognition, since most of what is sold at the street markets in Goiânia is produced in Goiás, so that family farming in the state can be valued and strengthened. It is hoped that the analyzes presented here will contribute to highlight the potential for valuing and participating in family farming in the food composition of Goianienses in relation to dairy products.